Music Community, Improvisation, and Social Technologies in COVID-Era Música Huasteca - Margolies, Daniel S.; Strub, J. A. (Frontiers in Psychology, 2021)
This article examines two interrelated aspects of Mexican regional music response to the coronavirus crisis in the música huasteca community: the growth of interactive huapango livestreams as a pre-existent but newly-significant space for informal community gathering and cultural participation at the onset of the coronavirus pandemic, and the composition of original verses by son huasteco performers addressing the pandemic. Both the livestreams and the newly created covid verses reflect critical improvisatory approaches to the pandemic in música huasteca. The interactive livestreams signaled an ad-hoc community infrastructure facilitated by social media and an emerging community space fostered by Do-It-Yourself (DIY) activists. Improvised covid-related verses presented resonant local and regional themes as a community response to a global crisis. Digital ethnography conducted since March, 2020 revealed a regional burst of musical creativity coupled with DIY intentionality, a leveling of access to virtual community spaces, and enhanced digital intimacies established across a wide cultural diaspora in Mexico and the United States. These responses were musically, poetically, and organizationally improvisational, as was the overall outpouring of son huasteco music inspired by the coronavirus outbreak. Son huasteco is a folk music tradition from the Huasteca, a geo-cultural region spanning the intersection of six states in central Mexico. This study examines a selection of musical responses by discussing improvisational examples in both Spanish and the indigenous language Nahuatl, and in the virtual musical communities of the Huasteca migrant diaspora in digital events such as “Encuentro Virtual de Tríos Huastecos,” the “Huapangos Sin Fronteras” festival and competition, and in nightly gatherings on social media platforms developed during the pandemic to sustain Huastecan cultural expression. These phenomena have served as vibrant points of transnational connection and identity in a time where physical gatherings were untenable.